Reverse extraction of protocol model from network applications. (1st January 2013) - Li, Meijian; Wang, Yongjun; Jin, Shangjie; Xie, Peidai
The reverse extraction of the protocol model from a network application is performed to understand network behaviour and detect vulnerabilities. In this paper, we propose a framework that automatically extracts the described formal protocol model using a state machine. The proposed system, which is based on a dynamic binary analysis technique, is suited to the reverse analysis of network applications implemented with closed and encrypted protocols. We evaluate the technique by conducting experiments on the extracting protocol models from two secure socket layer implementation programs to demonstrate the strength of this technique. The results show that the proposed approach can produce a corresponding approximate protocol model from network applications. However, exhibiting high practice in the aspect of network behaviour analysis does not make sense for real-world applications.